PENINGKATAN PROFESIONALME GURU DALAM MEMBUAT SOAL HOTS MELALUI KEGIATAN IHT DI SDN 001 NONGSA KOTA BATAM TAHUN PELAJARAN 2018/2019 - Choiriatun, Dwi (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2020)
Regarding the problems in SDN 001 Nongsa, there is a need for adequate handling assistance. In this case, the effort made is to carry out In House Training (IHT) activities, which aim at improving teacher professionalism through a systematic cycle. Data analysis was carried out using qualitative descriptive analysis. The research was conducted in cyclic stages, each cycle consisting of 4 (four) steps including: planning, implementing, observing and reflecting. The results of this study, 6 teachers from the schools who were the research subjects, all showed an increase in competence according to the predetermined success indicators. The suggestions put forward are: (1) it is necessary to intensify the professional improvement of teachers in making HOTS questions through IHT activities or the like (2) to improve the professionalism of teachers, schools, there needs to be IHT activities carried out not only in the school environment but also at the KKG level, so that they can exchange experiences through academic dialogue.